Emergency Department Management in Lazio, Italy. (January 2016) - Leo, Gianmaria; Lodi, Andrea; Tubertini, Paolo; Di Martino, Mirko
Abstract: The assignment of service requests to emergency departments is of paramount importance both from a life-threatening and an economical viewpoints. In the process of a more general project that aims at defining optimal allocation policies of patients to regional hospital network facilities (together with the potential reorganization of the facilities), the Department of Epidemiology of the Regional Health Service of Lazio, Italy, was interested in obtaining a completely offline picture of the effect of an optimal assignment of requests to emergency departments. This is in the spirit of evaluating the so-called Price of Anarchy, where the fully centralized (admittedly unrealistic) allocation is used as a reference for both the state-of-the-art completely decentralized approach and future reorganization ideas. We have implemented and tested with real-world data of all service requests of 2012 a mixed-integer programming model that computes such an optimal request allocation by minimizing travel and waiting times and penalizing workload unbalance among emergency departments in the region. Within the development process we have studied special cases and relaxations of the complete model showing interesting mathematical properties that are, in turn, useful from a practical viewpoint, for example, in obtaining a real-time version of the approach. The present study is an important, quantitative step in the evaluation of centralized allocation strategies like remote triage that could have a remarkable impact in making the allocation process much more efficient and effective. More precisely, the developed methodology as well as the software tools are currently used by the DEP-Lazio for the reorganization of the regional networks of emergency healthcare. Abstract : Highlights: Offline optimal assignment of requests to emergency departments. Comparison of centralized allocation and state-of-the-art decentralized one. Travel and waiting times minimization and regional workload unbalance penalization. Currently used by the DEP-Lazio for the reorganization of the ED regional network.